Hubungan Pengetahuan Ibu Hamil Tentang Proses Persalinan dengan Tingkat Kecemasan di Ruang VK RSUD Sele Be Solu Kota Sorong - Simon, Merlis; Rina; Gita, Wa ode (Jurnal Kesehatan, 2023)
Anxiety is a state where a person experiences feelings of restlessness, fear, worry, and discomfort accompanied by physical complaints. If anxiety is excessive, the impact that occur could inhibit normal cervical dilatation, resulting in prolonged labor and increased perception of pain and resulting in bleeding during labor and fetal distress, because the mother is too worried about her condition. Knowledge has an important role in the occurrence of anxiety levels. The purpose of this study was to determine the relationship between the knowledge of pregnant women about the delivery process and the level of anxiety in the VK Room of Sele Be Solu Hospital, Sorong City. The research method was quantitative with a cross sectional design. The study population was 50 patients. The sample of this study were 41 patients. This research was conducted in the VK room of Sele Be Solu Hospital, Sorong City, from September to October 2022. The results of the chi square test showed that there was a relationship between pregnant women’s knowledge about birth process and the anxiety levels (p value=0.004). The conclusion is that there is a relationship between the knowledge of pregnant women about the delivery process and the level of anxiety in the VK room of Sele Be Solu Hospital, Sorong City. From this study, it is hoped that the role of health workers especially midwives or nurses, could provide comprehensive information about the birth process that will be faced by pregnant women and the impact of anxiety on maternal labor.